Association between nadir albumin concentration and mortality in pediatric patients undergoing postcardiotomy extracorporeal membrane oxygenation - Liu, Qindong; Jin, Yu; Gao, Tianyu; Wang, He; Liu, Jia; Liu, Yue; Ji, Bingyang; Liu, Jinping (Translational Pediatrics, 2026)
Albumin is a key protein essential for maintaining multiple physiological functions. During extracorporeal membrane oxygenation (ECMO) support, serum albumin concentration may decline as a result of hemodilution or capillary leakage. This reduction may be more pronounced in pediatric patients, whose hepatic synthetic function is not fully mature. However, evidence regarding the association between serum albumin concentration and clinical outcomes in pediatric postcardiotomy ECMO patients remains limited. This study aims to explore this association in pediatric patients.